Rumyang Cirebon Mask Dance with Palimanan Style as a Door of Liminality Based on Victor Turner's Theory Perspective - Eza Kusuma Putri; Nursilah Nursilah (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
This research aims to describe and analyze the Palimanan Style Rumyang Mask Dance using the Theory of Liminality based on the thoughts of Victor Turner. This study uses the Qualitative Content Analysis method because the results of this study are in the form of described sentences. The object of this research is the Palimanan Style Rumyang Mask Dance. The cornerstone of the theory used in this study is Victor Turner's Theory of Liminality in analyzing the Palimanan Style Cirebon Rumyang Mask Dance. Data collection using interviews, observations, document studies and library studies. Data collection uses data triangulation techniques. The results obtained in this study are data descriptions, namely data on the presentation form of The Cirebon Palimanan Style Rumyang Mask Dance including: motion, makeup, fashion, accompaniment music, property and floor design. Palimanan Style Rumyang Mask Dance Data is interpreted based on Victor Turner's theory of Liminality with 3 cycles, namely the Pre liminal stage when the dancer has not danced the rumyang mask, the Liminal stage when the dancer pulls the Mask rumyang Cirebon Palimanan Style, and the last stage is Post Liminal after the dancer pulls the Mask Rumyang Cirebon Palimanan Style. Based on the results and discussions, it can be concluded in the Mask Dance of Rumyang Cirebon Palimanan Style There are 3 cycles of Liminality Theory. and the last stage is Post Liminal after the dancer pulls the Mask Rumyang Cirebon Palimanan Style. Based on the results and discussions, it can be concluded in the Mask Dance of Rumyang Cirebon Palimanan Style There are 3 cycles of Liminality Theory. and the last stage is Post Liminal after the dancer pulls the Mask Rumyang Cirebon Palimanan Style. Based on the results and discussions, it can be concluded in the Mask Dance of Rumyang Cirebon Palimanan Style There are 3 cycles of Liminality Theory.